THE EFFECTIVENESS AND IMPACT OF RSPO CERTIFICATIONS ON SUSTAINABILITY PRACTISES IN THE PALM OIL INDUSTRY: A CASE STUDY IN PT XYZ - Harsono, Satria Budi; Anggoro, Yudo (CV. Radja Publika, 2025)
This research examines the effectiveness and impact of RSPO (Roundtable on Sustainable Palm Oil) certification on sustainability practices in the palm oil industry, focusing on PT XYZ as a case study. As a downstream company utilizing the RSPO Supply Chain Certification with the Mass Balance model, PT XYZ sources Certified Sustainable Palm Oil (CSPO) and Certified Sustainable Palm Kernel Oil (CSPKO) from growers, aiming to align its business operations with global sustainability standards. The research analyzes the extent to which RSPO certification has promoted sustainable practices, contributed to environmental protection, and supported business growth within the context of Indonesia’s palm oil sector. The findings indicate that RSPO certification has enabled PT XYZ to enhance supply chain transparency, access premium international markets, and support the broader adoption of sustainable palm oil. Industry wide evidence shows RSPO certified supply chains contribute to reduced greenhouse gas emissions, improved peatland conservation, and lower fire risk. However, challenges remain regarding full traceability and the inclusion of smallholders. The study concludes that while RSPO certification is an effective mechanism for advancing sustainability in the palm oil industry, continuous improvement, stakeholder collaboration, and enhanced transparency are essential for maximizing its impact.